CLASSIFICATION OF RISKS OF MULTICULTURAL EDUCATION IN MONOETHNIC AND MULTIETHNIC ENVIRONMENT - SINYAGINA, NATALYA; GEVORGYAN , MAYRANUSH (Main Issues Of Pedagogy And Psychology, 2017)
This article is focused on the risks of multicultural education taking into account the ethnic composition of the region. The authors substantiate the relevance of multicultural education based on the results of empirical research conducted in high schools of Armenia and Russia. It is noted that the development and implementation of pedagogical models and programs of multicultural education are calculated only positive results, in real conditions of practice, it is impossible to avoid the risks. Identified and substantiated the following risks of multicultural education: strategical, risks of disagreement, dispositional, personality, psychological, communicative, technological, social-cultural risks.